OFF-GRID SOLAR PHOTOVOLTAIC (PV) DESIGN BASED ON FUZZY TECHNIQUE FOR ORDER PERFORMANCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) APPROACH - NUR AFIQAH, JAHILAN (Universiti Malaysia Sarawak (UNIMAS), 2022)
The primary energy source, fossil fuels are finite and the other alternative energy sources are costly. Due to this, the solar sector is constantly growing worldwide to generate tremendous demand for electrification. PV technology comprises the grid-connected PV systems and off-grid PV systems. Off-grid PV systems generate and distribute electrical energy independently, unlike the grid-connected PV systems. In this project, the modelling of the off-grid PV system is presented via LabVIEW graphical programming. The design process involved studies on the major components associated with the offgrid PV system such as the PV modules, batteries, solar charge controllers, and inverters to meet the load demand. Specifications and sizing of these PV components play a crucial role to prevent the most common issues in PV system design which are the under and oversizing. Thus, an optimum sizing technique is implemented in this project to overcome the said issue. The aforementioned technique is the MCDM method, particularly the fuzzy TOPSIS algorithm. This algorithm is embedded in the PV system to select the best PV components’ configuration based on multiple criteria. To add, the multiple criteria being utilized in the algorithm consists of benefit criteria and cost criteria. Precisely, the fuzzy TOPSIS algorithm has selected the best configuration of PV system with financial optimization feature. Moreover, this project also stressed the graphical user interface design for the off-grid PV system. The designed GUI displayed the input and output data of the PV system, assisted the user to enter input values for the required PV parameters, and allowed the user to perform data analysis for the PV system design. To summarize, the off-grid PV system designed in LabVIEW is viable and readily available for future use.